1980
DOI: 10.3109/03093648009103113
|View full text |Cite
|
Sign up to set email alerts
|

Skin problems of the leg amputee

Abstract: The importance of early recognition and treatment of skin lesions on the stumps of amputees cannot be overemphasized. Heavy demands are placed on the stump skin by the artificial limb. Even a minor skin eruption may, through neglect or mistreatment, become an extensive disorder that will seriously threaten the amputee's mental, social, and economic rehabilitation. Contact dermatitis, eczemas, epidermoid cysts, bacterial and fungus infections, chronic ulcers, and verrucose hyperplasia are among the disorders to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…Confinement of the stump in the socket and friction can cause skin maceration leading to folliculitis, eczema, or mycosis. Epidermoid cysts may develop in the subcutaneous tissue as a consequence of the implantation of keratin islets during surgery (26,29). Aggressive bone edge and heterotopic ossification may lead to ulceration.…”
Section: Cutaneous Lesionsmentioning
confidence: 99%
“…Confinement of the stump in the socket and friction can cause skin maceration leading to folliculitis, eczema, or mycosis. Epidermoid cysts may develop in the subcutaneous tissue as a consequence of the implantation of keratin islets during surgery (26,29). Aggressive bone edge and heterotopic ossification may lead to ulceration.…”
Section: Cutaneous Lesionsmentioning
confidence: 99%
“…Suitable pressure distribution within the lower-limb prosthetic socket is important for the comfort and function of the amputee [ 1 – 3 ], and an adequately fitting socket is required for extensive use of a functional prosthesis [ 4 ]. Inappropriate sockets have been implicated in cases of dermatological issues [ 5 , 6 ] and pressure injury [ 7 , 8 ]. Furthermore, socket comfort and socket fit are widely cited by users as the most important factor in their satisfaction with a prosthetic lower limb [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…If pressure, suction or infection is not the causative agent of damage it might be hypersensitivity reactions to materials simply labelled eczema. These different categories of skin lesions of stumps have been especially dealt with by Levy (1980). We found that scar problems were common during the early period and the other skin problems increased with time ( Table 1).…”
Section: Discussionmentioning
confidence: 91%